Polymer electrolyte membrane, membrane-electrode assembly including the polymer electrolyte membrane, and fuel cell
By using a high equivalent of the second ionomer and a low equivalent of the first ionomer in the gas inlet and outlet portion of the polymer electrolyte membrane, the polymer electrolyte membrane with a multi-layer structure is solved. The polymer electrolyte membrane in the fuel cell is solved. The deterioration and desorption problems improve chemical or mechanical durability and conductivity, and reduce resistance loss and cost.
Patent Information
- Application Number
- CN202180006878.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-16
- Filing Date
- 2021-09-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-09-17
AI Technical Summary
The existing polymer electrolyte membranes are susceptible to deterioration and desorption caused by gas pressure when the fuel cell is running, resulting in reduced chemical durability and insufficient mechanical strength, which affects conductivity and economic efficiency.
By using a second ionomer with a relatively high equivalent in the gas inlet and outlet portion of the polymer electrolyte membrane, a first segment with improved chemical or mechanical durability is formed, in combination with a first ionomer with a lower equivalent, A polymer electrolyte membrane with a multi-layer structure is formed.
Effectively prevent the deterioration and desorption of polymer electrolyte membranes, improve chemical or mechanical durability, reduce the reduction of hydrogen ion conductivity, reduce resistance loss, and improve the overall performance and economic efficiency of fuel cells.
Smart Images

Figure CN114730900B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a polymer electrolyte membrane, a membrane-electrode assembly including the polymer electrolyte membrane, and a fuel cell, and more particularly, to a polymer electrolyte membrane having improved chemical or mechanical durability by using an ionomer having a relatively high equivalent weight (EW) in a first stage, a membrane-electrode assembly including the polymer electrolyte membrane, and a fuel cell. Background Art
[0002] A fuel cell is a cell that directly converts chemical energy generated by oxidation of a fuel into electrical energy, and has attracted attention as a next-generation energy source due to its high energy efficiency and environmentally friendly characteristics with little pollutant emission.
[0003] Generally, a fuel cell has a structure in which an anode and a cathode are respectively formed on both sides of an electrolyte membrane interposed therebetween, and this structure is called a membrane-electrode assembly (MEA).
[0004] According to the type of electrolyte membrane, fuel cells can be divided into alkaline electrolyte membrane fuel cells, polymer electrolyte membrane fuel cells (PEMFC), etc. Among them, polymer electrolyte membrane fuel cells have attracted attention as portable, vehicle and home power supply devices due to their advantages such as low operating temperature below 100°C, fast startup and response characteristics, and excellent durability.
[0005] Typical examples of such polymer electrolyte membrane fuel cells may include proton exchange membrane fuel cells (PEMFCs) using hydrogen as fuel.
[0006] To summarize the reactions that occur in a polymer electrolyte membrane fuel cell, first, when a fuel such as hydrogen is supplied to the anode, hydrogen ions and electrons are generated by an oxidation reaction of hydrogen at the anode. The generated hydrogen ions are transferred to the cathode through the polymer electrolyte membrane, and the generated electrons are transferred to the cathode through an external circuit. Oxygen is supplied to the cathode, and the oxygen combines with the hydrogen ions and electrons to generate water through a reduction reaction of the oxygen.
[0007] Since the polymer electrolyte membrane is a channel through which hydrogen ions generated at the anode are transported to the cathode, the conductivity of hydrogen ions should be fundamentally excellent. In addition, the polymer electrolyte membrane requires the following characteristics, which should have excellent separation ability of hydrogen supplied to the anode and oxygen supplied to the cathode, in addition to excellent mechanical strength, dimensional stability, chemical resistance, etc., and small resistance loss (ohmic loss) at high current density.
[0008] As the polymer electrolyte membrane currently used, there is a perfluorosulfonic acid resin (hereinafter referred to as a "fluorine-based ion conductor") as a fluorine-based resin. However, since the mechanical strength of the fluorine-based ion conductor is weak, pinholes are generated when used for a long time, thereby causing a problem of reduced energy conversion efficiency. In order to enhance the mechanical strength, attempts have been made to use the fluorine-based ion conductor by increasing the film thickness, but in this case, the resistance loss increases, and the use of expensive materials also increases, so there is a problem of reduced economic efficiency.
[0009] In order to solve these problems, a polymer electrolyte membrane (or reinforced composite membrane) has been proposed, which has improved mechanical strength by impregnating a porous polytetrafluoroethylene resin (trade name: Teflon) (hereinafter referred to as "Teflon resin") as a fluorine-based resin with a liquid fluorine-based ion conductor. In this case, the hydrogen ion conductivity is slightly reduced compared to a polymer electrolyte membrane made of only a fluorine-based ion conductor, but since the mechanical strength is relatively excellent, the thickness of the electrolyte membrane can be reduced, thereby having an advantage of reduced resistance loss.
[0010] Meanwhile, when the fuel cell is in operation, the reinforced composite membrane corresponding to the gas inlet and / or the gas outlet is subjected to gas pressure, causing degradation and desorption of the reinforced composite membrane, thereby causing a problem of reduced chemical durability. In order to solve this problem, research is being continued on improving chemical durability while ensuring high ionic conductivity of the polymer electrolyte membrane. Summary of the invention
[0011] Technical issues
[0012] An object of the present disclosure is to provide a polymer electrolyte membrane, a membrane-electrode assembly including the polymer electrolyte membrane, and a fuel cell, wherein the polymer electrolyte membrane is improved in chemical or mechanical durability by preventing degradation and desorption of the polymer electrolyte membrane when the fuel cell is operated by using a second ionomer having a relatively higher EW than a polymer electrolyte membrane including a first ionomer in a portion corresponding to a gas inlet and / or a gas outlet.
[0013] Another object of the present disclosure is to form a polymer electrolyte membrane from a first ionomer having a relatively low EW, and to provide a segment including a second ionomer having excellent chemical durability on a portion susceptible to degradation and desorption, thereby preventing a decrease in hydrogen ion conductivity.
[0014] Another object of the present disclosure is to provide a method of manufacturing a polymer electrolyte membrane, which is capable of manufacturing a polymer electrolyte membrane having improved chemical or mechanical durability while using existing process equipment as it is.
[0015] The purpose of the present disclosure is not limited to the above-mentioned purpose, and other purposes and advantages of the present disclosure that are not mentioned can be understood by the following description, and will be more clearly understood by the embodiments of the present disclosure. In addition, it will be apparent that the purposes and advantages of the present disclosure can be achieved by the means indicated in the claims and their combinations.
[0016] Technical Solution
[0017] In order to achieve the above-mentioned purpose, a polymer electrolyte membrane according to one embodiment of the present disclosure is a polymer electrolyte membrane comprising a porous support and a composite layer containing a first ionomer filled in the porous support, wherein the polymer electrolyte membrane is equivalent to a polymer electrolyte membrane comprising a first segment having a first durability and a second segment having a second durability, and the first durability is higher than the second durability.
[0018] In order to achieve the above-mentioned purpose, a membrane-electrode assembly according to an embodiment of the present disclosure includes: a first electrode; a second electrode; and a polymer electrolyte membrane including a composite layer, which is inserted between the first electrode and the second electrode and includes a porous support and a first ionomer filled in the porous support, wherein the polymer electrolyte membrane includes a first segment having a first durability and a second segment having a second durability, and the first durability is higher than the second durability.
[0019] In order to achieve the above-mentioned purpose, a fuel cell according to an embodiment of the present disclosure includes: a first diaphragm; a second diaphragm; and a membrane-electrode assembly inserted between the first diaphragm and the second diaphragm, wherein the first electrode is arranged between the first diaphragm and the polymer electrolyte membrane, the first diaphragm includes a first inlet for supplying a first gas to the first electrode, a first outlet for the first gas and a first flow channel between the first inlet and the first outlet, and the first section corresponds to a section equivalent to the first inlet or the first outlet.
[0020] Beneficial Effects
[0021] According to the present disclosure, a polymer electrolyte membrane having improved chemical or mechanical durability by preventing degradation and desorption of the polymer electrolyte membrane when a fuel cell is operated can be provided. According to the present disclosure, a polymer electrolyte membrane having improved chemical or mechanical durability can be provided when using existing process equipment as it is.
[0022] In addition to the above-described effects, specific effects of the present disclosure will be described below while explaining specific contents for implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1shows a plan view of a polymer electrolyte membrane according to one embodiment of the present disclosure;
[0024] Figure 2 shows a side view of a polymer electrolyte membrane according to one embodiment of the present disclosure;
[0025] Figure 3 A fuel cell according to one embodiment of the present disclosure is shown;
[0026] Figure 4 An OCV maintenance test of each of the membrane-electrode assemblies including the polymer electrolyte membranes according to Example 1 and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0027] According to one embodiment of the present disclosure, there is provided a polymer electrolyte membrane, comprising: a porous support; and a composite layer comprising a first ionomer filled in the porous support, wherein the polymer electrolyte membrane comprises a first segment having a first durability and a second segment having a second durability, and the first durability is higher than the second durability.
[0028] Hereinafter, various configurations of the present disclosure will be described in more detail so that a person skilled in the art to which the present disclosure pertains can easily implement, but this is merely an example, and the scope of the present disclosure is not limited by the following contents.
[0029] The polymer electrolyte membrane according to the present disclosure may include a composite layer, which includes a porous support and a first ionomer filled in the porous support. Specifically, the first ionomer dispersion with high dispersion stability not only has excellent impregnation performance, but also has a small and uniform particle size. Therefore, when the first ionomer dispersion is impregnated and coated on a porous support to form a reinforced composite membrane-type polymer electrolyte membrane, the ionic conductivity of the polymer electrolyte membrane in both the plane direction and the thickness direction can be improved by enabling a water channel that provides a hydrogen ion movement path to be well formed in the thickness direction and in the plane direction. In this specification, the composite layer can be equivalent to a reinforced composite membrane.
[0030] Hereinafter, the configuration of the present disclosure will be described in more detail.
[0031] The porous carrier according to the present invention is made of an aggregate of three-dimensional irregular and discontinuously connected nanofibers, and therefore includes a plurality of uniformly distributed pores. The porous carrier composed of a plurality of uniformly distributed pores has excellent porosity and properties (such as dimensional stability), which can complement the physical properties of the ion conductor.
[0032] The pore size is the diameter of the pores formed in the porous carrier, which can be formed in the range of 0.05μm to 30μm (micrometers), and when the pore size is smaller than the above numerical range, the ionic conductivity of the polymer electrolyte will decrease, and when it exceeds the above numerical range, the mechanical strength of the polymer electrolyte will decrease.
[0033] The porosity indicates the degree of formation of pores of the porous support and can be formed in the range of 50% to 98%. When the porosity of the porous support is less than the above range, the ion conductivity of the polymer electrolyte is reduced, and when it exceeds the above range, the mechanical strength and shape stability of the polymer electrolyte are deteriorated.
[0034] The porosity (%) can be calculated by the ratio of the volume of air to the total volume of the porous support, as shown in Equation 1 below.
[0035] [Equation 1]
[0036] Porosity (%) = (air volume / total volume) × 100
[0037] At this time, the total volume of the porous support is calculated by preparing a sample of a porous support having a rectangular shape and measuring the width, length and thickness of the sample, and after measuring the mass of the sample of the porous support, the polymer volume calculated by reverse calculation from the density can be obtained by subtracting the measured mass of the sample of the porous support from the total volume of the porous support.
[0038] The porous support is made of an aggregate of three-dimensional irregular and discontinuously connected nanofibers, and the average diameter of the nanofibers may be in the range of 0.005 μm to 5 μm (micrometers). When the average diameter of the nanofibers is less than the above numerical range, the mechanical strength of the porous support may deteriorate, and when it exceeds the above numerical range, it may be difficult to control the porosity of the porous support.
[0039] The nanofiber may be any one selected from nylon, polyimide, polybenzoxazole, polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene, poly(arylethersulfone), polyetheretherketone, copolymers thereof, and combinations thereof, but the technical concept of the present disclosure is not limited thereto.
[0040] The porous support may be formed to have a thickness of 5 to 30 μm (micrometers). When the thickness of the porous support is less than the above thickness range, the mechanical strength and morphological stability of the polymer electrolyte may be reduced, and when it exceeds the above thickness range, the resistance loss of the polymer electrolyte may increase.
[0041] The porous support may include a perfluorinated polymer [e.g., polytetrafluoroethylene (PTFE), or tetrafluoroethylene and CF2=CFC] having high resistance to thermal and chemical decomposition. n F2n+1 (n is a real number from 1 to 5) or CF2=CFO-(CF2CF(CF3)O) m C n F 2n+1 (m is a real number of 0 to 15, and n is a real number of 1 to 15)]. As another example, a commercially available stretched polytetrafluoroethylene membrane (e-PTFE membrane) can be used as the porous support.
[0042] The porous support according to the present disclosure may correspond to a nonwoven web formed of a polymer for forming a nonwoven web. For example, the porous support may be a nanoweb in which nanofibers having an average diameter of 40 nm to 5,000 nm are randomly arranged.
[0043] The polymer used to form the nonwoven web may correspond to a polymer having excellent chemical resistance and having no concern about shape deformation due to moisture in a high humidity environment.
[0044] For example, the polymer used to form the nonwoven web can be an aliphatic polyamide, an aromatic polyamide, a polyimide, a polyetherimide, a polyacrylonitrile, a polyaniline, a polyethylene oxide, a polyethylene naphthalate, a polybutylene terephthalate, a styrene-butadiene rubber, a polystyrene, a polyvinyl chloride, a polyvinyl alcohol, a polyvinylidene fluoride, a polyvinyl butyral, a polyurethane, a polybenzoxazole, a polybenzimidazole, a polyamideimide, a polyethylene terephthalate, a polyphenylene sulfide, a polyethylene, a polypropylene, a copolymer of two or more thereof, or a mixture of two or more thereof.
[0045] In particular, polyimide is one of the preferred candidate materials for forming the porous support because of its excellent heat resistance, chemical resistance, and morphological stability.
[0046] The composite layer according to the present disclosure may include a first ionomer filled in a porous support. Specifically, the composite layer may include a first surface and a second surface opposite to the first surface. That is, the first surface and the second surface may refer to, for example, surfaces opposite to each other, and may refer to the upper surface and the lower surface of the composite layer, respectively.
[0047] A polymer electrolyte membrane according to another embodiment of the present disclosure may include: a first resin layer disposed on the first surface; and a second resin layer disposed on the second surface. The first resin layer and the second resin layer may include the first ionomer.
[0048] The resin layer is an ionomer layer that is additionally added to both surfaces of the composite layer separately from the first and second sections according to the present disclosure.
[0049] Figure 1A plan view of a polymer electrolyte membrane according to an embodiment of the present disclosure is shown.
[0050] Figure 2 A side view of a polymer electrolyte membrane according to one embodiment of the present disclosure is shown.
[0051] In the following, for the convenience of description, reference will be made to Figure 1 and Figure 2 The configuration of the present disclosure is described in detail.
[0052] Reference Figure 1 and Figure 2 , the polymer electrolyte membrane 34 according to the present disclosure may include a first segment SEG1 having a first durability and a second segment SEG2 having a second durability. The first durability is characterized in that it is higher than the second durability. In this specification, durability may refer to chemical or mechanical durability.
[0053] Specifically, the first segment SEG1 may include a first sublayer sub1 and a second sublayer sub2 disposed on the first sublayer sub1. That is, the first segment SEG1 may include at least two sublayers.
[0054] For example, the first segment SEG1 may have a double-layer structure including a first sublayer sub1 and a second sublayer sub2, and the second segment may have a single-layer structure. At this time, the first sublayer sub1 and the second segment SEG2 may include a first ionomer, and the second sublayer sub2 may include a second ionomer. The durability of the second ionomer may be higher than that of the first ionomer.
[0055] According to one embodiment of the present disclosure, the first sub-layer sub1 and the second segment SEG2 may be arranged side by side.
[0056] The second sub-layer sub2 may be directly disposed on the first sub-layer sub1, and preferably, no element is interposed between the first sub-layer sub1 and the second sub-layer sub2.
[0057] The first ionomer may be a fluorine-based ionomer, more preferably a perfluorosulfonic acid (PFSA)-based ionomer. The second ionomer may include a fluorine-based ionomer, or a mixture of a hydrocarbon-based ionomer and a fluorine-based ionomer.
[0058] The mixture of hydrocarbon ionomer and fluorine ionomer may correspond to, for example, a mixture of perfluorosulfonic acid (PFSA) and hydrocarbon ionomer.
[0059] The hydrocarbon ionomer may include, for example, one or more selected from sulfonated polyimide (S-PI), sulfonated polyarylethersulfone (S-PAES), sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (SPBI), sulfonated polysulfone (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene ether, sulfonated polyethersulfone, sulfonated polyetherketone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylether, sulfonated polyarylether nitrile, sulfonated polyarylether ether nitrile and sulfonated polyarylether sulfoneketone.
[0060] The first ionomer may include a first fluorine-based ionomer, and the second ionomer may include a second fluorine-based ionomer. The first fluorine-based ionomer and the second fluorine-based ionomer may be fluorine-based polymers containing at least one cation exchange group selected from sulfonic acid group, carboxyl group, boric acid group, phosphoric acid group, imide group, sulfonimide group, sulfonamide group, sulfonic acid fluoride group and their derivatives.
[0061] For example, the fluorine-based polymer may be poly(perfluorosulfonic acid), poly(perfluorocarboxylic acid), a copolymer of tetrafluoroethylene and fluorovinyl ether containing a sulfonic acid group, defluorinated sulfurized polyetherketone, or a mixture of two or more thereof.
[0062] The fluorine-based polymer can be an anion conductor having an anion exchange group. Specifically, the anion conductor is a polymer capable of transmitting anions such as hydroxide ions, carbonate or bicarbonate. As an anion conductor, a polymer doped with a metal hydroxide can generally be used, specifically, poly(ether sulfone), polystyrene, vinyl polymer, poly(vinyl chloride), poly(vinylidene fluoride), poly(tetrafluoroethylene), poly(benzimidazole) or poly(ethylene glycol) doped with a metal hydroxide can be used.
[0063] The equivalent weight (EW) of the second fluorine-based ionomer may be greater than the EW of the first fluorine-based ionomer. Specifically, the second fluorine-based ionomer and the first fluorine-based ionomer may have an EW difference equivalent to 100 g / eq to 500 g / eq.
[0064] The first fluorine-based ionomer may include a perfluorosulfonic acid (PFSA)-based ionomer having an EW of 600 to 800 g / eq, and the second fluorine-based ionomer may include a PFSA-based ionomer having an EW of 900 to 1,100 g / eq.
[0065] Meanwhile, in one embodiment of the present disclosure, the first ionomer constituting the second segment SEG2 may include a third fluorine-based ionomer, and the second ionomer may include a mixture of a fourth fluorine-based ionomer and a hydrocarbon ionomer. The ion exchange capacity (IEC) of the second ionomer may be 0.8 meq / g to 1.9 meq / g.
[0066] The mixture of the fourth fluorine-based ionomer and the hydrocarbon-based ionomer may have an ion exchange capacity (IEC) equivalent to 0.8 meq / g to 1.9 meq / g, and when the ion exchange capacity (IEC) exceeds the above numerical range, the ion conductivity of the polymer electrolyte membrane may decrease.
[0067] The third fluorine-based ionomer and the fourth fluorine-based ionomer may be fluorine-based polymers including at least one cation exchange group selected from sulfonic acid group, carboxyl group, boric acid group, phosphoric acid group, imide group, sulfonimide group, sulfonamide group, sulfonic acid fluoride group and derivatives thereof.
[0068] In one embodiment of the present disclosure, the third fluorine-based ionomer and the fourth fluorine-based ionomer may be the same as or different from each other. Specifically, when the third fluorine-based ionomer and the fourth fluorine-based ionomer are different from each other, the third fluorine-based ionomer and the fourth fluorine-based ionomer may each independently include a perfluorosulfonic acid-based ionomer having an EW of 500 g / eq to 1,100 g / eq.
[0069] Specifically, the EW of the third fluorine-based ionomer is preferably 600 g / eq to 800 g / eq. Since the fourth fluorine-based ionomer is mixed with a hydrocarbon ionomer for improving strength, it may have an EW value of 600 g / eq or less. That is, the EW of the fourth fluorine-based ionomer is preferably 500 g / eq to 1,100 g / eq, and more preferably 700 g / eq to 900 g / eq.
[0070] The first ionomer can be used to improve the physical durability of the fuel cell system, thereby forming a reinforced composite membrane, which is another type of polymer electrolyte membrane. Specifically, the reinforced composite membrane can be made by impregnating a porous support with a first ionomer dispersion as part of improving the mechanical durability of a polymer electrolyte membrane in the form of a single layer membrane.
[0071] The reinforced composite membrane may be composed of a porous support for improving dimensional stability, durability, mechanical strength, etc., which are disadvantages of a single electrolyte membrane, together with an ion conductor as an electrolyte material. Specifically, the first ionomer may have a low equivalent weight (EW) value in order to ensure high ionic conductivity of the polymer electrolyte.
[0072] Meanwhile, when the fuel cell is in operation, when the reinforced composite membrane is subjected to pressure from the first section corresponding to the gas inlet and / or the gas outlet of the anode plate, there is a problem of degradation and desorption of the reinforced composite membrane containing the first ionomer, thereby reducing the chemical durability of the reinforced composite membrane and degrading the performance of the fuel cell.
[0073] Specifically, the reinforced composite membrane including the first ionomer is thermally stable up to 150° C. due to the strong C-F bond and the shielding effect of the electronegative fluorine atoms, and begins to deteriorate at a temperature above 150° C., so that the sulfonic acid group as a side chain is broken at a high temperature above 280° C. Electrochemical degradation of the polymer electrolyte membrane is caused by hydrogen peroxide and free radicals formed when hydrogen and oxygen passing through the membrane meet on the catalyst. That is, hydrogen peroxide and free radicals destroy the bonds between the polymers constituting the first ionomer, thereby reducing battery performance and life.
[0074] An object of the present disclosure is to improve chemical or mechanical durability by suppressing the deterioration reaction as described above.
[0075] To solve this problem, the polymer electrolyte membrane according to the present disclosure may be equivalent to a polymer electrolyte membrane having improved chemical or mechanical durability by further including a first segment coated with a second ionomer in a segment corresponding to a gas inlet and / or a gas outlet of an anode plate.
[0076] Specifically, the improvement of chemical degradation of the polymer electrolyte membrane according to the present disclosure can be confirmed through hydrogen permeability, OCV accelerated durability evaluation, and accompanying fluoride ion release rate (FER) tests.
[0077] When the hydrogen permeability is measured, it can be inferred that the polymer electrolyte membrane according to the present disclosure exhibits a lower value of hydrogen permeability compared to a polymer electrolyte membrane using only the first fluorine-based ionomer without using the second fluorine-based ionomer.
[0078] For example, when open circuit voltage (OCV) durability is measured, the polymer electrolyte membrane according to the present disclosure can show higher OCV durability than a polymer electrolyte membrane using only the first fluorine-based ionomer without using the second fluorine-based ionomer. OCV durability can be calculated by the change of OCV (V) over time (hours).
[0079] The fluoride ion release rate (FER) test is a test for measuring the fluorine outflow rate by performing an OCV accelerated test on the polymer electrolyte membrane. The polymer electrolyte membrane according to the present disclosure shows a higher value of battery life than the polymer electrolyte membrane using only the first fluorine-based ionomer, from which it can be inferred that the chemical durability will be improved.
[0080] Specifically, the second ionomer is characterized by having a relatively higher EW value than the first ionomer. The higher the EW value, the lower the ionic conductivity, but the chemical or mechanical durability of the portion of the polymer electrolyte membrane corresponding to the gas inlet and / or the gas outlet containing the second ionomer can be improved.
[0081] Based on one surface of the polymer electrolyte membrane, the first segment may occupy less than 50% of the total active area, and the first segment is preferably 5% to 40% of the total active area of the polymer electrolyte membrane. More preferably, 10% to 30% is appropriate. When the area of the first segment is less than the area of the above numerical range, the effect of improving the chemical or mechanical durability of the polymer electrolyte membrane cannot be exhibited, and when it is greater than the area of the above numerical range, the hydrogen ion conductivity of the polymer electrolyte membrane will decrease.
[0082] The method for manufacturing a polymer electrolyte membrane according to the present disclosure may include the steps of manufacturing an electrolyte membrane by impregnating a porous support in a first ionomer dispersion and then drying it; and forming a first section by coating a second ionomer on a portion of a surface of the dried electrolyte membrane corresponding to a gas inlet and / or a gas outlet of an anode plate of a fuel cell, wherein the second ionomer may have a relatively higher EW value than the first ionomer.
[0083] A conventional method of manufacturing a polymer electrolyte membrane may include the steps of casting a dispersion containing an ionomer, placing a porous support in a dry state on the dispersion so that the entire porous support is in a wet state, and drying the wet porous support.
[0084] The polymer electrolyte membrane according to the present disclosure may be manufactured by further including a step of coating a second ionomer in the existing manufacturing method.
[0085] Specifically, as described above, the following steps are performed: casting a dispersion containing the first ionomer and placing a porous support in a dry state on the dispersion, so that the porous support is in a wet state as a whole. Thereafter, the first segment can be formed by coating the second ionomer on the region where the first segment is to be formed.
[0086] More specifically, the step of forming the first segment may include: coating the second ionomer by any one selected from a spraying method and a lamination method.
[0087] The thickness of the first segment SEG1 may be 5 μm to 100 μm (micrometers), preferably 7 μm to 60 μm (micrometers). The thickness of the second sub-layer sub2 may be preferably 1 μm to 10 μm (micrometers).
[0088] At the same time, there may be a step difference between the second segment SEG2 and the first segment SEG1, and the step difference may be 1 μm to 10 μm (micrometers). More preferably, the step difference may be 1 μm to 5 μm (micrometers). When the step difference exceeds the above step difference range, problems may arise in terms of electrode transfer uniformity of the membrane-electrode assembly and tightening pressure deviation during battery tightening.
[0089] The spraying method refers to coating the second ionomer on the first segment using a sprayer, and the lamination method refers to a technique of protecting the surface and improving strength and stability by thinly covering the first segment with the second ionomer. The second sublayer sub2 may be, for example, a single layer or multiple layers, and the technical concept of the present disclosure is not limited to the number of layers.
[0090] Specifically, the spraying method can be performed by, for example, flatly fixing the treated porous support to a mold manufactured into a predetermined shape and spraying the second ionomer dispersion at a predetermined distance using an ultrasonic spray gun. The second ionomer dispersion can be sprayed at a flow rate of about 1 ml / sec to 1,000 ml / sec at a frequency of about 20 to 130. When the second ionomer is sprayed onto the porous support, it is preferably sprayed substantially in the direction of gravity. In this case, the direction in which the second ionomer dispersion is sprayed is substantially the same as the direction of gravity, so that the impregnation force can be maximized when the spraying method is performed.
[0091] The lamination method refers to a manufacturing method in which the second ionomer is thermally transferred to the first stage by a laminating roller constituting the machine using a laminating machine.
[0092] The temperature for thermally transferring the second ionomer to the first stage using the laminating roller is preferably 80 to 160° C., more preferably 90 to 130° C. When the temperature exceeds the above numerical range, there is a problem that the fluorine-based ionomer decomposes due to heat.
[0093] In addition, the step of forming the first segment can be introduced into a production line of an R2R (roll-to-roll) process which is one of the processes for manufacturing a reinforced composite film without requiring an additional process, so that there is an advantage that manufacturing costs can be saved.
[0094] The porous support may be formed by dissolving a precursor in a spinning solvent to prepare a spinning solution, spinning the prepared spinning solution to manufacture a porous nanonet composed of nanofibers having an average diameter of 0.005 μm to 5 μm (micrometers), and then performing a post-treatment process on the manufactured nanonet.
[0095] The porous support is preferably prepared by an electrospinning process to obtain high porosity, small pores and a thin film, but the technical concept of the present disclosure is not limited thereto.
[0096] The porous support may be prepared by spinning any one selected from nylon, polyimide, polybenzoxazole, polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene, polyarylethersulfone, polyetheretherketone, copolymers thereof, and combinations thereof.
[0097] In the following, reference will be made to Figures 1 to 3 The configuration of the present disclosure is described.
[0098] Figure 3A fuel cell according to one embodiment of the present disclosure is shown.
[0099] Reference Figures 1 to 3 , the membrane-electrode assembly 35 according to one embodiment of the present disclosure may include: a first electrode 32; a second electrode 33; and a polymer electrolyte membrane 34 according to a partial embodiment inserted between the first electrode 32 and the second electrode 33. Specifically, the first electrode 32 may be a cathode where a reduction reaction of oxygen occurs, and the second electrode 33 may be an anode where an oxidation reaction of hydrogen occurs. The polymer electrolyte membrane is the same as the polymer electrolyte membrane according to one embodiment of the present disclosure described above, and repeated description will be omitted.
[0100] A fuel cell 39 according to another embodiment of the present disclosure may be characterized in that it includes: a first diaphragm 31; a second diaphragm 37; and a membrane-electrode assembly 35 inserted between the first diaphragm 31 and the second diaphragm 37, wherein the first electrode 32 is arranged between the first diaphragm 31 and the polymer electrolyte membrane 34, the first diaphragm 31 includes a first inlet for supplying a first gas to the first electrode 32, a first outlet for the first gas and a first flow channel between the first inlet and the first outlet, and the first segment SEG1 is a segment corresponding to the first inlet or the first outlet.
[0101] The fuel cell according to another embodiment of the present disclosure may further include a gas diffusion layer between the above-mentioned separator and the cell. Since it is obvious to those skilled in the art, a detailed description of the gas diffusion layer will be omitted.
[0102] Hereinafter, embodiments of the present disclosure will be described in detail so that those skilled in the art to which the present disclosure pertains can easily implement the present disclosure, but these are merely examples, and the scope of the present disclosure is not limited to the following contents.
[0103] [Manufacturing Example 1: Manufacture of polymer electrolyte membrane]
[0104] Polymer electrolyte membranes according to the following Comparative Example 1 and Examples 1 to 3 were manufactured.
[0105] <Comparative Example 1>
[0106] After preparing an ionomer dispersion containing 20 wt% of a fluorine-based polymer (perfluorosulfonic acid; PFSA) having an equivalent weight (EW) of 600 g / eq, a porous support (e-PTFE, pore size: 0.10 μm to 0.15 μm, thickness: 6 μm, tensile elongation (MD / TD): 1.1) was impregnated therein, and then dried at 60° C. for 1 hour to prepare a composite layer. Thereafter, the same ionomer dispersion was additionally applied on both surfaces of the composite layer, and then a polymer electrolyte membrane was manufactured by first drying at 60° C. for 1 hour and second drying at 150° C. for 30 minutes.
[0107] <Example 1>
[0108] After preparing an ionomer dispersion containing 20 wt% of a fluorine-based polymer (perfluorosulfonic acid; PFSA) having an equivalent weight (EW) of 600 g / eq, a porous support (e-PTFE, pore size: 0.10 μm to 0.15 μm, thickness: 6 μm, tensile elongation (MD / TD): 1.1) was impregnated therein, and then dried at 60° C. for 1 hour to prepare a composite layer. Thereafter, the same ionomer dispersion was additionally applied to both surfaces of the composite layer, and then a polymer electrolyte membrane was manufactured by first drying at 60° C. for 1 hour and second drying at 150° C. for 30 minutes. Thereafter, a fluorine-based polymer (perfluorosulfonic acid; PFSA) having an equivalent weight (EW) of 900 g / eq was additionally applied to the edge portions corresponding to the gas inlet and the gas outlet of both surfaces of the polymer electrolyte membrane corresponding to the first section using a spray method (device: spray gun, spacing: 10 cm, spray amount: 1 ml / min). Thus, a second sublayer having a thickness of 5 μm was formed on each of the edge portions of both surfaces of the polymer electrolyte membrane.
[0109] <Example 2>
[0110] A polymer electrolyte membrane was manufactured in the same manner as in Example 1 except that a second sublayer having a thickness of 2 to 3 μm was formed on edge portions of both surfaces of the polymer electrolyte membrane using a heat lamination method with a heat roll temperature of 150° C. instead of a spraying method.
[0111] <Example 3>
[0112] A polymer electrolyte membrane was manufactured in the same manner as in Example 1, except that a mixture of perfluorosulfonic acid (PFSA) and sulfonated polyetheretherketone (SPEEK) in a weight ratio of 1:1 (ion exchange capacity: 1.0 meq / g) was used instead of the fluorine-based polymer having an equivalent weight (EW) of 900 g / eq.
[0113] [Manufacturing Example 2: Manufacturing of a membrane-electrode assembly]
[0114] A membrane-electrode assembly was manufactured by directly coating the electrode slurry on both surfaces of the polymer electrolyte membrane according to Manufacturing Example 1. The electrode slurry contained Pt / C and a binder (PFSA) mixed at a weight ratio of 3:2.
[0115] [Experimental Example 1: OCV maintenance test of membrane-electrode assembly]
[0116] The chemical durability of the membrane-electrode assembly according to the above-mentioned Manufacturing Example 2 was evaluated. Specifically, after evaluating the hydrogen permeability (LSV method) every 100 hours under the scheme (90°C, 30RH, 50kPa, An=H2 / Ca=air), if it increased by more than 10 times compared with the initial value, or the OCV loss was more than 20%, the evaluation was terminated.
[0117] Figure 4 An OCV maintenance test of each of the membrane-electrode assemblies including the polymer electrolyte membranes according to Example 1 and Comparative Example 1 is shown.
[0118] Reference Figure 4 It can be seen that the membrane-electrode assembly including the polymer electrolyte membrane according to Comparative Example 1 rapidly loses 20% of OCV over time, compared with the OCV loss of the membrane-electrode assembly including the polymer electrolyte membrane according to Example 1. It can be confirmed that chemical durability is improved by introducing the first section corresponding to the gas inlet and the gas outlet.
[0119] In the case of the membrane-electrode assembly including the polymer electrolyte membrane according to Example 2 and Example 3, Figure 4 The OCV retention test was carried out under the same scheme as in the above, and the results shown in Table 1 below were obtained.
[0120] [Table 1]
[0121]
[0122] Referring to Table 1 above, it can be confirmed that, in the degradation process of the membrane-electrode assembly including the polymer electrolyte membrane according to Examples 1 to 3, it takes a long time (hours) for the OCV loss to reach 20% compared to the membrane-electrode assembly including the polymer electrolyte membrane according to Comparative Example 1. It can be confirmed that the chemical durability of the membrane-electrode assembly including the polymer electrolyte membrane according to Examples 1 to 3 is significantly improved compared to that according to Comparative Example 1. Specifically, comparing Example 1 with Example 3, it can be inferred that the effect of chemical durability is greater when the second sublayer is made of a mixture of a hydrocarbon ionomer and a fluorine ionomer than when the second sublayer is made of a fluorine ionomer having a relatively large equivalent.
[0123] Hereinabove, exemplary embodiments of the present disclosure have been described in detail, but the scope of the present disclosure is not limited thereto, and various changes or modifications by those skilled in the art using the basic concept of the present disclosure defined in the following claims also fall within the scope of the present disclosure.
Claims
1. A fuel cell, comprising: First diaphragm; Second diaphragm; and a membrane-electrode assembly interposed between the first diaphragm and the second diaphragm, Wherein, the membrane-electrode assembly comprises: a first electrode; a second electrode; and a polymer electrolyte membrane interposed between the first electrode and the second electrode, wherein the first electrode is disposed between the first diaphragm and the polymer electrolyte membrane, wherein the first diaphragm comprises a first inlet for supplying a first gas to the first electrode, a first outlet for the first gas, and a first flow channel between the first inlet and the first outlet, Wherein, the polymer electrolyte membrane comprises: a porous support; and a composite layer comprising a first ionomer filled in the porous support, wherein the polymer electrolyte membrane comprises a first section having a first durability and a second section having a second durability, and the first durability is higher than the second durability, The first paragraph includes: a first sublayer and a second sublayer disposed on the first sublayer, wherein the second section has a single-layer structure, wherein the first sublayer and the second segment comprise a first ionomer, wherein the second sublayer comprises a second ionomer, and the durability of the second ionomer is higher than the durability of the first ionomer, Wherein, the first ionomer comprises a first fluorine-based ionomer, The second ionomer comprises a mixture of a second fluorine-based ionomer and a hydrocarbon-based ionomer, The first section is a section corresponding to the first inlet or the first outlet, wherein the first sublayer and the second segment are arranged side by side, Wherein, the thickness of the second sublayer is 1 μm to 10 μm, and Wherein, based on one surface of the polymer electrolyte membrane, the first segment occupies 5% to 40% of the total active area.
2. The fuel cell according to claim 1, wherein The second ionomer has an ion exchange capacity (IEC) of 0.8 meq / g to 1.9 meq / g.
3. The fuel cell according to claim 1, wherein: The first fluorine-based ionomer and the second fluorine-based ionomer each independently include a perfluorosulfonic acid-based ionomer having an EW of 500 g / eq to 1,100 g / eq.
4. The fuel cell according to claim 3, wherein: The EW of the first fluorine-based ionomer is 600 g / eq to 800 g / eq, and the EW of the second fluorine-based ionomer is 500 g / eq to 1,100 g / eq.
5. The fuel cell according to claim 4, wherein: The EW of the second fluorine-based ionomer is 700 g / eq to 900 g / eq.
6. The fuel cell according to claim 1, wherein The hydrocarbon ionomer includes one or more selected from sulfonated polyimide (S-PI), sulfonated polyarylethersulfone (S-PAES), sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (SPBI), sulfonated polysulfone (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene ether, sulfonated polyethersulfone, sulfonated polyetherketone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylether, sulfonated polyarylether nitrile, sulfonated polyarylether ether nitrile and sulfonated polyarylether sulfoneketone.
7. The fuel cell according to claim 1, wherein The first fluorine-based ionomer and the second fluorine-based ionomer are the same as each other.
8. The fuel cell according to claim 1, wherein The composite layer includes: a first surface and a second surface opposite to the first surface, and the polymer electrolyte membrane also includes: a first resin layer disposed on the first surface; and a second resin layer disposed on the second surface, and the first resin layer and the second resin layer contain the first ionomer.
Citation Information
Patent Citations
Polymer electrolyte membrane, method for manufacturing same, and membrane electrode assembly comprising same
CN111164813A
Membranes and electrochemical cells incorporating such membranes
CN1965425A
Membrane-electrode assembly and fuel cell having it
JP2008146859A
Non-homogeneous polymer electrolyte composite membranefor fuel cell and method to prepare the same
KR1020060083372A
Polymer electrolyte membrane, and membrane electrode assembly and polymer electrolyte fuel cell using the same
US20120107721A1